The Other Side of the Story Structures and Strategies of Contemporary Feminist Narratives - Hite, Molly (Cornell University Press, 2018)
According to Molly Hite, a number of influential contemporary women novelists-notably Jean Rhys, Doris Lessing, Alice Walker, and Margaret Atwood-attempt innovations in narrative form that are more radical in their implications than the dominant modes of fictional experimentation characterized as postmodernist. In The Other Side of the Story, Hite makes the point that these innovations, which distinguish the genre she calls contemporary feminist narrative, are more radical precisely because their context is the critique of a culture and a literary tradition apprehended as profoundly masculinist.